Chemical Composition and Anti-Candidiasis Mediated Wound Healing Property of Cymbopogon nardus Essential Oil on Chronic Diabetic Wounds - Kandimalla, Raghuram; Kalita, Sanjeeb; Choudhury, Bhaswati; Dash, Suvakanta; Kalita, Kasturi; Kotoky, Jibon (Frontiers in Pharmacology, 2016)
Poor wound healing is one of the major complication of diabetic patients which arises due to different factors like hyperglycemia, oxidative stress, vascular insufficiency and microbial infections. Candidiasis of diabetic wounds is a difficult to treat condition and potentially can lead to organ amputation. There are a few number of medications available in market to treat this chronic condition; which demands for alternative treatment options. In traditional system of medicine like Ayurveda, essential oil extracted from leaves of Cymbopogon nardus L. (Poaceae) has been using for the treatment of microbial infections, inflammation and pain. In this regard, we have evaluated anti-Candida and anti-inflammatory activity mediated wound healing property of C. nardus essential oil (EO-CN) on candidiasis of diabetic wounds. EO-CN was obtained through hydro-distillation and subjected to Gas chromatography mass spectroscopy (GC-MS) analysis for chemical profiling. Anti-Candida activity of EO-CN was tested against C. albicans, C. glabrata and C. tropicalis by in-vitro zone of inhibition and minimum inhibitory concentration (MIC) assays. Anti-candidiasis ability of EO-CN was evaluated on C. albicans infected diabetic wounds of mice through measuring candida load on the 7th, 14th and 21st day of treatment. Further progression in wound healing was confirmed by measuring the inflammatory marker levels and histopathology of wounded tissues on last day of EO-CN treatment. A total of 95 compounds were identified through GC-MS analysis, with major compounds like citral, 2,6-octadienal- 3,7-dimethyl-, geranyl acetate, citronellal, geraniol and citronellol. In vitro test results demonstrated strong anti-Candida activity of EO-CN with a MIC value of 25 µg/ml against C. albicans, 50 µg/ml against C. glabrata and C. tropicalis. EO-CN treatment resulted in significant reduction of candida load on diabetic wounds. Acceleration in wound healing was indicated by declined levels of inflammatory cytokines at wounded area in EO-CN treated animals compared to non-treated group, which was further confirmed by histopathological examination. This study suggests that through significant anti-Candida and anti-inflammatory activity, EO-CN attenuates the growth of the fungus on diabetic wounds and simultaneously reduces the inflammation which leads to acceleration of the wound healing process.